2021
DOI: 10.3389/fneur.2021.659890
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Vessel Responses to Flicker Stimulation Are Impaired in Cav2.3-Deficient Mice—An in-vivo Evaluation Using Retinal Vessel Analysis (RVA)

Abstract: Objective: Metabolic demand increases with neuronal activity and adequate energy supply is ensured by neurovascular coupling (NVC). Impairments of NVC have been reported in the context of several diseases and may correlate with disease severity and outcome. Voltage-gated Ca2+-channels (VGCCs) are involved in the regulation of vasomotor tone. In the present study, we compared arterial and venous responses to flicker stimulation in Cav2.3-competent (Cav2.3[+/+]) and -deficient (Cav2.3[−/−]) mice using retinal ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The above-mentioned processes cumulatively result in dysfunction of NVC following aSAH. Preclinical and clinical studies have indeed revealed dysregulation of vasodilatation and even pathological vasoconstriction in response to different stimuli in experimental aSAH models and patients (Britz et al, 2007;Budohoski et al, 2012;Koide et al, 2013a;Balbi et al, 2017;Neumaier et al, 2021). Moreover, DCI has been associated with decreased vasoreactivity of the middle cerebral artery measured 4 to 10 days after ictus in a prospective clinical study including 34 patients with aSAH (Carrera et al, 2010).…”
Section: Phase Iv: Neurovascular Uncouplingmentioning
confidence: 96%
“…The above-mentioned processes cumulatively result in dysfunction of NVC following aSAH. Preclinical and clinical studies have indeed revealed dysregulation of vasodilatation and even pathological vasoconstriction in response to different stimuli in experimental aSAH models and patients (Britz et al, 2007;Budohoski et al, 2012;Koide et al, 2013a;Balbi et al, 2017;Neumaier et al, 2021). Moreover, DCI has been associated with decreased vasoreactivity of the middle cerebral artery measured 4 to 10 days after ictus in a prospective clinical study including 34 patients with aSAH (Carrera et al, 2010).…”
Section: Phase Iv: Neurovascular Uncouplingmentioning
confidence: 96%
“…Throughout the last years DVA has been adjusted to be used in rodents. Only recently a study was able to prove an involvement of voltage-gated calcium channels in knock-out mice 21 . Further in-vivo studies in rodents are needed to clarify the role of inflammation in the pathophysiology of retinal microvascular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of NO synthase during isometric exercise in healthy humans reduced retinal venous diameter and responsiveness ( 51 ). Recently, the application of a prototype of an adapted RVA in laboratory animals was introduced to evaluate neurovascular coupling in the murine retina ( 52 , 53 ).…”
Section: Methods Of Measurementmentioning
confidence: 99%